A Case Study of an EFL Teacher’s Implementation of Role-Play Strategy in Teaching Speaking at a Junior High School - Berliana Delima Citra; Abdul Kodir Al-Baekani; Dedeh Kartini (Universitas Islam Negeri Palopo, 2026)
This study examines how an English as a Foreign Language (EFL) teacher implements role-playing strategies in speaking instruction at the junior high school level for the first time. By examining the experiences of a novice teacher, this study provides critical insights into how teachers adapt innovative strategies in real classroom contexts an essential dimension for understanding the development of sustainable teaching practices and serving as input for teacher training programs. Using a qualitative case study approach, data were collected through classroom observations over three sessions and semi-structured interviews. The analysis revealed five sequential phases of implementation scenario planning, instruction, role assignment, facilitation, and feedback along with four pedagogical considerations: pronunciation development, student confidence, teacher readiness, and curriculum alignment. These findings indicate that the successful implementation of role-playing heavily depends on teachers’ pedagogical readiness and adaptive decision-making, thereby providing concrete implications for the design of professional development programs that support novice EFL teachers in adopting communicative strategies. This study addresses a significant research gap by shifting the focus from learning outcomes to the implementation process itself, thereby contributing to a more contextually relevant EFL pedagogy in junior high schools in Indonesia.